2021
DOI: 10.20944/preprints202105.0730.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Cellular Stress in Intrauterine Growth Restriction and Postnatal Dysmetabolism

Abstract: Disruption of the in utero environment can have dire consequences on fetal growth and development. Intrauterine growth restriction (IUGR) is a pathological condition by which the fetus deviates from its expected growth trajectory, resulting in low birth weight and impaired organ function. The developmental origins of health and disease (DOHaD) postulates that IUGR has lifelong consequences on offspring well-being, as human studies have established an inverse relationship between birth weight and long-term meta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 113 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Impaired immune responses may also lead to metabolic diseases in individuals with FGR [12]. A high-throughput RNA sequencing analysis based on the FGR sheep model showed that the transcriptome responsible for B cell dysfunction was involved in immune response, WNT signal 4 transduction, and adaptive stress response pathways [13].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired immune responses may also lead to metabolic diseases in individuals with FGR [12]. A high-throughput RNA sequencing analysis based on the FGR sheep model showed that the transcriptome responsible for B cell dysfunction was involved in immune response, WNT signal 4 transduction, and adaptive stress response pathways [13].…”
Section: Introductionmentioning
confidence: 99%